Steroid-Responsive Recurrent Encephalopathy Associated with Subacute Thyroiditis - Chung, Yun Jae (Korean Neurological Association, 2008)
BACKGROUND: Steroid-responsive encephalopathy associated with subacute thyroiditis has, to our knowledge, not been reported previously. CASE REPORT: A 49-year-old woman was found collapsed and brought to our institution with decreased mentality, dysarthria, and gait disturbance. Brain magnetic resonance imaging and angiography were normal but blood tests revealed thyroid-autoantibody-negative thyrotoxicosis. Results of a (99m)technetium-pertechnetate scan were compatible with the thyrotoxic phase of subacute thyroiditis. 14-3-3 proteins were detected in cerebrospinal fluid. Her mental status began to improve from the day following steroid administration. Recurrent encephalopathy was found 2 months after the initial admission, which was also effectively treated with steroid. CONCLUSIONS: We speculate that steroid-responsive recurrent encephalopathy associated with subacute thyroiditis is a subtype of Hashimoto's encephalopathy, and consider that steroid treatment should not be delayed in suspected patients.